Energy Efficient Design of Power‑to‑Gas Generation Systems for Circular Economy - Winkler, Wolfgang G. (New Energy Exploitation and Application, 2025)
Generous subsidies and “technological openness” cannot fulfill European goals of affordability, environmental compatibility, and security of supply as recent blackouts and rising grid fees show. A clear structured definition of development targets based on TRL (Technological Readiness Level) is needed as used in aerospace industry. Affordability and security of supply provide the guidelines for a CO2 emission free system design. Energy transition will only work with a sufficient storable thermodynamic potential that guarantees power generation at any time with a cost‑effective energy storage technology. While H2 suffers from its low volumetric energy density and high cost a Closed Carbon Cycle (CCC) based on CH4 and C2H4 delivers an energy density up to more than 16 times higher than H2 with increasing carbon content. High thermodynamic system integration, including heat pumps and electrochemical O2 removal during the hydrocarbon‑forming reaction, increases efficiency. Electrolyzers and CH4/C2H4 forming reactors can be integrated in a steam generator design to optimize internal heat transfer and allow variable pressures. The conversion efficiency is estimated at up to 90% and a reconversion efficiency like pump storage hydro power plants. The concept fits very well with the current infrastructure of natural gas. It can supply industry with renewable hydrocarbons and use plastic waste for recovery. “Green fuels” can be delivered by using CO2 from bio‑energy utilization. H2 can be additionally generated by reforming like today with natural gas. Conversion efficiency, electricity price, full load operation hours, and investment cost mainly influence the gas price.